Co-production of 1, 2, 4-butantriol and ethanol from lignocellulose hydrolysates. (June 2019) - Zhao, Meilin; Shi, Dingchang; Lu, Xinyao; Zong, Hong; Zhuge, Bin
Highlights: C. glycerinogenes UG21 was used to degrade glucose and furfural in hydrolysates. Sugarcane bagasse-based BT production was realized by microbial fermentation. BT production reached 4.9 g/L. Co-production of ethanol and BT was achieved. Abstract: The aim of this work was to realize 1, 2, 4-butantriol (BT) production from sugarcane bagasse hydrolysates by microbial fermentation, and obtain co-production of BT and ethanol. Candida glycerinogenes UG21 was utilized to reduce the effect of osmolality resulting from high glucose concentration and furfural in hydrolysates on cell growth of BT-producing strains, and produced 54.1 g/L ethanol from glucose. After ethanol recovering, xylose containing stillage was obtained and used for BT production. 1.3 g/L BT was generated by a BT-producing strain. By the deletion of the crr gene and process optimization, BT titer reached 4.9 g/L. Meanwhile, the efficient utilization of sugarcane bagasse was achieved by a two-stage fermentation for co-production of BT and ethanol. This study provided a novel strategy for BT production from sugarcane bagasse, and demonstrated the potential for making full use of sugarcane bagasse hydrolysates to co-production value-added products.